Recent Advances in Radical Fluorination - Chatalova-Sazepin, Claire; Hemelaere, Rémy; Paquin, Jean-François; Sammis, Glenn M. (Synthesis, 2015)
The importance of fluorinated compounds in pharmaceutical, agrochemical, and material chemistry has led to the development of numerous methods for electrophilic and nucleophilic fluorination. Radical fluorination represents an interesting complementary approach, but it had been limited due to the paucity of selective radical fluorinating agents. The recent uncovering of easier to handle atomic fluorine sources has led to significant advances in radical fluorination in the past few years. This review presents the newly developed methods for fluorination involving radicals as reactive intermediates.1 Introduction2 Atomic Fluorine Sources2.1 Fluorine as a Selective Radical Fluorinating Agent2.2 Fluoroxy Reagents2.3 XeF22.4 N–F Reagents as Atomic Fluorine Sources3 Methodologies for Radical Fluorination3.1 Decarboxylative Fluorination3.2 Fluorination of Alkenes3.3 Fluorination of Boronic Acid Derivatives3.4 C(sp3)–H Fluorination3.5 C–C Bond Activation4 Conclusion
Keywords: fluorination; radical chemistry; synthetic methods; C–H activation